Career Development of Civil Servants with the Implementation of the Merit System at the Secretariat General of the House of Representatives of the Republic of Indonesia - Silaban, Eriko; Syafri, Wirman; Nurdin, Ismail; Kawuryan, Megandaru W. (Technium Social Sciences Journal, 2024)
The merit system implementation in the environment of the General Secretariat of the House of Representatives of the Republic of Indonesia has reached a “Good” category. However, it has not achieved an ideal or maximum value as career development (54%) and information systems (54%) could be better. This research is a qualitative study with data obtained through observations and interviews of the parties involved in the career development policy of civil servants there. The analysis showed that civil servants' career development policy has gone well and is in line with the rules. However, one factor should be corrected or noted by the leadership, which is related to the fairness factor. This study proposes a policy model for the career development of civil servants called the SIMANTAP TIMBO Model. It is a simple system that includes evaluating civil officials' profiles or mechanisms for forming a talent pool and determining candidates who will occupy a position (successor office).